Anecdotes that provide definitive evidence. Issue 7581 (14th December 2006) - Aronson, Jeffrey K; Hauben, Manfred
Abstract : When a criminal is caught in the act, other evidence is unnecessary. Should the same be true for adverse drug reactions?